Computers into classrooms: More questions than answers (London, 1993)
This book examines computers and their uses in teaching and learning. It sets out to raise fundamental questions concerning the nature of 'technological literacy', a hitherto vague term. It provides a series of guidelines for teachers employing, or about to employ, computers in their classrooms
Keywords: computer - assisted instruction,instruction - aids and devices